Investigations of conjugate heat transfer and fluid flow in partitioned porous cavity using Darcy-Forchheimer model: Finite element-based computations - Nasir Yasin; Shafee Ahmad; Muhammad Umair; Zahir Shah; Narcisa Vrinceanu; Ghadah Alhawael (Case Studies in Thermal Engineering)
The conjugate heat transfer and fluid flow has vast applications in thermal engineering, particularly for cooling in thermal devices, and automobile engines. This study investigates conjugate heat transfer in 2D enclosures, featuring thin solid fins attached to a porous bottom wall. The porous medium is considered isotropic and homogeneous by the Darcy-Forchheimer model, with fluid phases in local thermal equilibrium. The boundary conditions at the porous fluid interface ensure continuity of the velocities, stresses, temperature, and heat flux. The phenomenon is mathematically modelled by obtaining a set of partial differential equations. The finite element method (FEM) is used to perform the simulation. Initially, the scheme is validated both experimentally and numerically for further computations. It is seen that increasing Reynolds number (Re) and Darcy number (Da), transforms flow from laminar to complex, enhancing thermal mixing and heat transfer efficiency through intricate streamlines and distorted isotherms. Conversely, higher fin heights reduce fluid velocities resulting in lower kinetic energy. The greater Nusselt number (Nu) is obtained near the solid block and becomes larger with its height. It is investigated that Numean leads to enhancement with thermal conductivity of the base plate. With the change in Re, the size and location of the primary vortex significantly changes.